Lessons from precision medicine in rheumatology. (April 2020) - Wampler Muskardin, Theresa L; Paredes, Jacqueline L; Appenzeller, Simone; Niewold, Timothy B
Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are two common autoimmune rheumatic diseases that vary in severity, clinical presentation, and disease course between individuals. Molecular and genetic studies of both diseases have identified candidate genes and molecular pathways that are linked to various disease outcomes and treatment responses. Currently, patients can be grouped into molecular subsets in each disease, and these molecular categories should enable precision medicine approaches to be applied in rheumatic diseases. In this article, we will review key lessons learned about disease heterogeneity and molecular characterization in rheumatology, which we hope will lead to personalized therapeutic strategies.